Normobaric hyperoxia inhibits the progression of lung cancer by inducing apoptosis. Issue 9 (May 2018) - Kim, Sei Won; Kim, In Kyoung; Ha, Jick Hwan; Yeo, Chang Dong; Kang, Hyeon Hui; Kim, Jin Woo; Lee, Sang Haak
Hypoxia is a critical characteristic of solid tumors with respect to cancer cell survival, angiogenesis, and metastasis. Hyperoxic treatment has been attempted to reverse hypoxia by enhancing the amount of dissolved oxygen in the plasma. In this study, we evaluated the effects of normobaric hyperoxia on the progression of lung cancer to determine whether oxygen toxicity can be used in cancer therapy. Following a tail vein injection of the Lewis lung carcinoma cells, C57BL/6J mice were exposed to a 24-h normobaric hyperoxia/normoxia cycle for two weeks. In addition, A549 lung cancer cells were incubated in a normobaric hyperoxia chamber for a 24-h period. As a result, the size and number of tumors in the lung decreased significantly with exposure to normobaric hyperoxia in the mouse model. Cell viability, colony-forming ability, migration, and invasion all decreased significantly in A549 cells exposed to normobaric hyperoxia and the normal control group exposed to normobaric hyperoxia showed no significant damage. Oxidative stress was more prominent with exposure to normobaric hyperoxia in cancer cells. A549 cells exposed to normobaric hyperoxia showed a significantly higher cell apoptosis ratio compared with A549 cells without normobaric hyperoxia exposure and normal human lung cells (BEAS-2B cells). The Bax/Bcl-2 mRNA expression ratio also increased significantly. Changes in the key regulators of apoptosis were similar between in vivo and in vitro conditions. The p-ERK level decreased, while the p-JNK level increased, after normobaric hyperoxia exposure in A549 cells. This study demonstrated the role of normobaric hyperoxia in inhibiting lung cancer. Normal tissue and cells showed no significant hyperoxic damage in our experimental setting. The anti-tumor effect of normobaric hyperoxia may due to the increased reactive oxygen species activity and apoptosis, which is related to the mitogen-activated protein kinase pathway. Impact statement: Normobaric hyperoxia (NBO) is a feasible therapy for cancer with a low complication rate. Although NBO may be beneficial in cancer treatment, very few studies have been conducted; thus, the evidence is thin. This is the first study to clearly demonstrate morphological changes in lung cancer with NBO exposure and to investigate the underlying mechanisms both in vivo and in vitro . This study will arouse interest in NBO treatment and promote further research.